A switch for epitaxial graphene electronics: Utilizing the silicon carbide substrate as transistor channel - Krach, Florian; Hertel, Stefan; Waldmann, Daniel; Jobst, Johannes; Krieger, Michael; Reshanov, S.; Schoner, A.; Weber, Heiko B. (Applied Physics Letters, 2012)
Due to the lack of graphene transistors with large on/off ratio, we propose a concept employing both epitaxial graphene and its underlying substrate silicon carbide (SiC) as electronic materials. We demonstrate a simple, robust, and scalable transistor, in which graphene serves as electrodes and SiC as a semiconducting channel. The common interface has to be chosen such that it provides favorable charge injection. The insulator and gate functionality is realized by an ionic liquid gate for convenience but could be taken over by a solid gate stack. On/off ratios exceeding 44000 at room temperature are found. © 2012 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.aswitc